Infantile Systemic Hyalinosis - Sharwari Jaiswal; Bhushan Madke; Meenakshi Chandak; Shivani Jangid (Wolters Kluwer Medknow Publications, 2024)
Infantile systemic hyalinosis (ISH) is a rare autosomal recessive disorder characterized by widespread hyaline deposition in various tissues, resulting in multi-organ dysfunction. We present a case of a 6-month-old male child with minimal limb movements and skin lesions, emphasizing the diagnostic challenges and multidisciplinary approach involved in managing ISH. Medical history revealed intrauterine growth retardation and a neonatal intensive care unit admission, prompting referral to a tertiary care hospital. A comprehensive evaluation, including imaging, electrophysiological studies, and histology, confirmed the diagnosis of ISH-associated myopathy. Dermatological manifestations and genetic implications are discussed, highlighting the need for early recognition and genetic counseling. Our case contributes to the limited literature on ISH, emphasizing the importance of collaborative efforts in diagnosing and managing this complex disorder.